2009
DOI: 10.1002/elps.200900078
|View full text |Cite
|
Sign up to set email alerts
|

Continuous particle separation based on electrical properties using alternating current dielectrophoresis

Abstract: A design of a microchannel for continuous separation of particles based on alternating current dielectrophoretic is studied. The geometric design parameters are determined by analyzing the dielectrophoresis force field inside the microchannel corresponding to the most efficient separation. The trajectories of 5 and 10 mm spherical particles are derived analytically using Lagrangian tracking method to examine the feasibility and the effectiveness of the design. The effects of the mean flow velocity inside the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…However, it has been shown that this method can predict the particle motion qualitatively. By introducing a scale factor which accounts for the distortion of the electric and flow fields due to the finite particle size, the simulation results can match the experimental results [10,11,45,46,50]. The scaling factor is assumed to be constant and varies between 0 and 1.0 for a given particle size.…”
Section: Modelingmentioning
confidence: 89%
See 3 more Smart Citations
“…However, it has been shown that this method can predict the particle motion qualitatively. By introducing a scale factor which accounts for the distortion of the electric and flow fields due to the finite particle size, the simulation results can match the experimental results [10,11,45,46,50]. The scaling factor is assumed to be constant and varies between 0 and 1.0 for a given particle size.…”
Section: Modelingmentioning
confidence: 89%
“…In this model, the particle is assumed to be move with a terminal velocity under the action of drag force which is the result of the interaction of the particle with the flow field, and the DEP force which is the result of the interaction of the particle with the electrical field. The details of the modeling of the particle motion can be found in our previous studies [46,50]. Considering the drag force and the DEP force, velocity of the particle can be written as…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Inlet velocity was calculated and chosen in simulations as 0.018 m/s to be able to apply 10 μL/min flow rate. Outlet boundary condition was chosen as zero pressure because it is open to atmosphere throughout the tests .…”
Section: Methodsmentioning
confidence: 99%